Personalised choice of antidepressants. The effects of sertraline, escitalopram, mirtazapine, venlafaxine and bupropion illustrated by clinical cases - Murawiec, Sławomir (Psychiatria Spersonalizowana / Personalized Psychiatry, 2024)
This paper presents some aspects of the pharmacotherapy of depression and anxiety disorders from both a theoretical and practical point of view. The first part presents the concepts of “drug-centred psychopharmacotherapy” and the cognitive neuropsychological theory of antidepressant action, and a summary of research on the effect of drugs on the processing of information about positive and negative emotional valence. The second part of the paper presents clinical vignettes of patients treated with escitalopram, sertraline, venlafaxine and mirtazapine. Differences in the profile of action of these drugs in comparison with buropion were also discussed. In the cases described here, the administration of the above-mentioned drugs proved to be beneficial in the subjective experience of the patients, while in the objective assessment it led to relief of depressive symptoms.